Hygiene Sanitasi di UPTD Puskesmas Kuala Lempuing Kota Bengkulu - Wulan Angraini; Henni Febriawati; Mohammad Amin (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Snacks that are not healthy in the community can cause diarrhea problems in the community. From the data from the UPTD of the Kuala Lempuing Health Center, diarrhea cases recorded from January-September 2021 were 94 cases with the lowest patient age range being 5-9 years old and the highest patient age 55-59 years old. The purpose of this health education is to look at the hygiene and sanitation of street food at the UPTD Puskesmas Kuala Lempuing. The method is to conduct health education in the community. Data collection using a questionnaire which was carried out on October 5 to d. 05 November 2021. The results of the data obtained from the questionnaire by calculating the average respondent's answer to each question which is then narrated. The results obtained will be conveyed to the street food seller and health education is carried out to increase knowledge of the snack food seller. The conclusion of this health education is that the application of Sanitary Hygiene can certainly lead to health and productivity for the community by increasing public knowledge about the application of food sanitation hygiene. Communities are able to prevent disease and create a healthy society. ABSTRAK Makanan jajanan yang tidak sehat di masyarakat dapat menyebabkan permasalahan diare di masyarakat. Dari data UPTD Puskesmas Kuala Lempuing kasus diare tercatat dari bulan Januari-September 2021 adalah 94 kasus dengan rentang umur penderita terendah berusia 5-9 tahun dan umur penderita tertinggi berusia 55-59 tahun. Tujuan dari pendidikan kesehatan ini adalah untuk melihat hygiene sanitasi pada makanan jajanan di UPTD Puskesmas Kuala Lempuing. Metodenya adalah dengan melakukan pendidikan kesehatan dimasyarakat. Pengumpulan data menggunakan kuesioner yang dilaksanakan pada 05 Oktober s.d. 05 November 2021. Hasil data diperoleh dari kuesioner dengan menghitung rata-rata jawaban responden dari setiap pertanyaan yang kemudian dinarasikan. Hasil yang didapat nantinya akan disampaikan kepada penjual makanan jajanan dan dilakukan pendidikan kesehatan untuk meningkatkan pengetahuan pada penjual makanan jajanan tersebut. Kesimpulan dari pendidikan kesehatan ini adalah penerapan Higiene Sanitasi tentu dapat menimbulkan kesehatan dan produktifitas bagi Masyarakat dengan meningkatnya pengetahuan masyarakat mengenai penerapan higiene sanitasi makanan. Masyarakat mampu mencegah penyakit dan terciptanya masyarakat yang sehat.